MODEL PILIHAN PENYELESAIAN SENGKETA HASIL PILKADA - Ari Nur Utomo; Malik Akbar Mulki Rahman (Al-Ijtima`i: International Journal of Government and Social Science, 2023)
Regional General Elections or often referred to as regional elections are a method or mechanism for electing regional heads that are based on the constitution and are legal according to law. With the regional election, it is hoped that a fair, honest and wise leader can be elected to form a democratic government, but in the process there are disputes over the results of the vote count so that it has the potential to cause conflict if not resolved quickly. To overcome this, the government appointed the Supreme Court which has the right to adjudicate the dispute, over time the authority was then transferred to the Constitutional Court, causing a tug of war against the authorities authorized to adjudicate disputes over the results of the elections. Therefore, the writing of this paper will try to provide a study that aims to provide input to the government to choose the right institution for adjudicating the results of regional election disputes. This writing uses a normative juridical method with a statutory, historical, and conceptual approach and is supported by primary and secondary data. The results of this paper have four recommendations for institutions that have the right to adjudicate regional elections including the Constitutional Court, High Administrative Court, Election Watchdog, and the Special Court.